Dari Eden ke Perjanjian Baru: Alkitab Menjawab Mengapa Saya Menikah - Sulistiono (Sekolah Tinggi Teologi Trinity Parapat, 2025)
This article aims to explain the theological reasons why humans marry, as set out in the biblical narratives from Genesis to the New Testament. Through a review of literature and a theological interpretive approach, it demonstrates that marriage is an integral part of the divine mandate and a reflection of God's love, rather than merely a social or biological necessity. It highlights that marriage is rooted in creation, love, character development and participation in God's mission on earth. Furthermore, it discusses key principles for building a Christian family, including the roles of husband and wife, effective communication, financial management, and spiritual development. The article concludes that a healthy Christian marriage can only be established on the true principles of God's word.